1988
DOI: 10.1148/radiology.167.2.3357944
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal nodes in bronchogenic carcinoma: comparison between CT and mediastinoscopy.

Abstract: Computed tomography (CT) and mediastinoscopy were compared in 151 patients with bronchogenic carcinoma. In all patients in whom findings at mediastinoscopy were negative, all accessible nodes were either removed or sampled at thoracotomy. Several size criteria for identifying nodes as enlarged on CT scans were compared. The long axis greater than or equal to 15 mm and short axis greater than 10 mm had very low sensitivity (61%), and the long axis greater than 5 mm had a low specificity (23%). CT (long axis gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
6

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(55 citation statements)
references
References 0 publications
5
44
0
6
Order By: Relevance
“…In 1984, LIBSHITZ and MCKENNA [105] demonstrated CT sensitivity and specificity of 67% and 66% respectively using a nodal size of 1 cm to distinguish between benign nodes and those seeded with metastases. In 1988 STAPLES et al [106] demonstrated 79% sensitivity and 65% specificity for CT using a 1-cm long axis nodal cut-off measurement. A meta-analysis in 1990 of 42 CT studies assessing mediastinal lymph node metastases from NSCLC described an overall sensitivity of 0.79, a specificity of 0.78 and an accuracy of 0.79 [107].…”
Section: Nodal Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1984, LIBSHITZ and MCKENNA [105] demonstrated CT sensitivity and specificity of 67% and 66% respectively using a nodal size of 1 cm to distinguish between benign nodes and those seeded with metastases. In 1988 STAPLES et al [106] demonstrated 79% sensitivity and 65% specificity for CT using a 1-cm long axis nodal cut-off measurement. A meta-analysis in 1990 of 42 CT studies assessing mediastinal lymph node metastases from NSCLC described an overall sensitivity of 0.79, a specificity of 0.78 and an accuracy of 0.79 [107].…”
Section: Nodal Statusmentioning
confidence: 99%
“…However, in 1992 MCLOUD et al [108] using a nodal short axis measurement of 1 cm in 143 patients, returned to less inspiring figures of 64% sensitivity and 62% specificity, respectively. These studies [105,106,108] all examined patients with presumed operable lung cancer in whom complete nodal sampling was performed either at mediastinoscopy or thoracotomy. Both LIBSHITZ and MCKENNA [105] and MCLOUD et al [108] observed an increase in false-positive nodes in patients with obstructive pneumonia.…”
Section: Nodal Statusmentioning
confidence: 99%
“…Imaging with CT and PET is neither sensitive nor specific enough to detect nodal metastasis. Several studies have compared CT to mediastinoscopy in the accurate staging of bronchogenic carcinoma [5] [6] [7]. A mediastinum that appears normal upon CT may harbor metastatic disease in 13% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Existen múltiples estudios 10,[19][20][21][22] que han intentado determinar la sensibilidad y especificidad de la TAC para el estadiaje ganglionar del cáncer de pulmón, obteniendo resultados no siempre congruentes. Una de las razones por la que existen estas diferencias es la decisión del tamaño que debe tener una adenopatía para considerarla sospechosa de malignidad.…”
Section: Sensibilidad Y Especificidad Según Nivel Ganglionarunclassified